2016
DOI: 10.18632/oncotarget.8998
|View full text |Cite
|
Sign up to set email alerts
|

The role of VDR and BIM in potentiation of cytarabine-induced cell death in human AML blasts

Abstract: Acute Myeloid Leukemia (AML) has grave prognosis due to aggressive nature of the disease, the toxicity of standard treatment, and overall low cure rates. We recently showed that AML cells in established culture treated with cytarabine (AraC) and a differentiation agent combination show enhancement of AraC cytotoxicity. Here we elucidate molecular changes which underlie this observation with focus on AML blasts in primary culture. The cells were treated with AraC at concentrations achievable in clinical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Accordingly, we confirmed that the depletion of VDR by partial knock down (KD) by either CRISPR/Cas9 or siRNA reduces ECD in HL60 cells ( Fig. 2A, and previous publications [2,16]) and in U937 cells (Suppl. Figs S2A, B).…”
Section: Knock Down Of Vdr By Crispr/cas9 or Sirna In Aml Cell Lines supporting
confidence: 89%
“…Accordingly, we confirmed that the depletion of VDR by partial knock down (KD) by either CRISPR/Cas9 or siRNA reduces ECD in HL60 cells ( Fig. 2A, and previous publications [2,16]) and in U937 cells (Suppl. Figs S2A, B).…”
Section: Knock Down Of Vdr By Crispr/cas9 or Sirna In Aml Cell Lines supporting
confidence: 89%
“…These compounds, an analog of vitamin D2 Doxercalciferol (D2) and a plant-derived antioxidant carnosic acid (CA), have a powerful differentiating effect when combined, and this increases the cytotoxicity of AraC to AML blasts. Importantly, this action is selective for neoplastic cells, as the enhancement of cell death by this differentiation agent combination has no observable effect on the normal bone marrow cells (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…The initial investigation of the mechanism responsible for the enhancement of AraC-induced cell death by treating cells that have damaged DNA with a differentiation agent combination (D2/CA) has revealed a paradoxical tumor suppressor-like activity of BRAF. We found that reducing the level or inhibiting the kinase activity of BRAF diminishes the ability of D2/CA to enhance ALM cell death (13). Also, D2/CA increases BRAF expression in a VDR-dependent manner, which correlates with the increased levels of the DNA damage marker H2AX (14).…”
Section: Introductionmentioning
confidence: 99%
“…To understand the basis of this resistance, we must first understand the ATRA-induced differentiation program. Toward this challenge, lessons learned in model systems, such as the lineage-uncommitted human myeloblastic cell line HL-60 reported to closely resemble patient derived cells 10 , could inform our analysis of the differentiation programs occurring in patients. Patient derived HL-60 leukemia cells have been a durable experimental model since the 1970’s to study differentiation 11 .…”
Section: Introductionmentioning
confidence: 99%